Inovasi Pembelajaran Matematika: Pengaruh Project-Based Learning Terhadap Hasil Belajar Satuan Panjang - Husna, Hikmatul; Widiyono, Aan; Sofiana, Nina (Griya Journal of Mathematics Education and Application, 2025)
Abstract This study aims to examine the extent to which the Project-based Learning (PjBL) model impacts mathematics learning outcomes on the topic of length units for third-grade students at SDN 2 Bendanpete. The research employs a quantitative experimental method through a Pre-Experimental Design approach, specifically using a One-Group Pretest-Posttest Design. The data analysis techniques include prerequisite tests through normality testing and hypothesis testing using the Paired Sample T-Test. Data were collected through multiple-choice tests administered before (pretest) and after (posttest) the implementation of the Project-based Learning (PjBL) model. Instrument validation results indicated that 15 items were valid, and reliability testing showed a high reliability score with Cronbach’s α = 0.860. Data analysis through the t-test, resulting in a value of (-19.0), demonstrated a significant improvement in student learning outcomes, with the average posttest score (81.1) considerably higher than the average pretest score (51.4). These findings suggest that the application of the PjBL model effectively enhances student achievement in the topic of length measurement. It is expected that the outcomes of this research will provide new insights into the use of innovative instructional models to improve student learning achievement. Keywords: Project-based Learning; Learning Outcomes; Mathematics